Developing a contextually and culturally relevant benefit-sharing framework for pathogen genomic research and biobanking in africa: a deliberative expert approach - Pamela Emefa Selormey; Irene H. Tsey; John Ganle; Patricia Akweongo; Paulina Tindana (BMC Medical Ethics)
Abstract Background Globally, researchers are struggling to implement benefit-sharing plans in genomics research and biobanking. In the African context, there are currently limited benefit-sharing frameworks to guide researchers, and some often rely on personal relationships and judgments in making decisions. Consequently, there have been calls for the development of contextually and culturally relevant benefit-sharing frameworks for pathogenic research and biobanking in Africa. This study responds to that call by using a deliberative experts approach to propose and develop a benefit-sharing framework for pathogen genomic research and biobanking. Methods Data were collected through deliberative expert key informant interviews. A total of 25 participants, comprising genomics researchers, policymakers, Nagoya Protocol Focal persons, members of institutional review boards, Sponsors and Experts in the field of genomics and biobanking were purposively sampled from 12 countries. Open-ended topic guides were designed and used to facilitate the interviews. The interviews explored issues such as the need for a benefit-sharing framework, the principles underpinning the practice of benefit-sharing, and key features of a possible benefit-sharing framework. Interviews were conducted in English, audio-recorded, and transcribed. Transcripts were imported into Nvivo 14 software, coded and analysed using the framework approach for qualitative data analysis. Results The participants reported on the key issues to consider in the development of a benefit-sharing framework. These included motivations for sharing benefits, key elements of a benefit-sharing framework and suggestions for monitoring the implementation of the framework. Based on these expert responses, we proposed and developed a three-phase framework. The first phase presents the contextual benefit-sharing process, which includes the benefit-sharing process, iterative benefit-sharing cycles and post-benefit-sharing responsibilities. The second phase comprises the implementation phase with templates on a step-by-step approach to achieving the three areas in phase 1 and the third concentrates on workplans to accommodate future emerging issues such as designing strategies to map out best practices on benefit-sharing, making efforts to publish the selected strategy and implementing the selected benefit-sharing. Conclusions The deliberative approach used in this study allowed for not only contextually and culturally relevant factors to be identified but also enabled reflexive decision-making. The framework developed has the potential to provide practical guidance to pathogen genomic stakeholders in the identification and implementation of benefit-sharing opportunities in their research programmes. More empirical studies are however required to test and evaluate the framework. Clinical trial number Not applicable.